2019
DOI: 10.1186/s13059-019-1857-2
|View full text |Cite
|
Sign up to set email alerts
|

eIF4A2 drives repression of translation at initiation by Ccr4-Not through purine-rich motifs in the 5′UTR

Abstract: Background: Regulation of the mRNA life cycle is central to gene expression control and determination of cell fate. miRNAs represent a critical mRNA regulatory mechanism, but despite decades of research, their mode of action is still not fully understood. Results: Here, we show that eIF4A2 is a major effector of the repressive miRNA pathway functioning via the Ccr4-Not complex. We demonstrate that while DDX6 interacts with Ccr4-Not, its effects in the mechanism are not as pronounced. Through its interaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 93 publications
2
66
1
Order By: Relevance
“…EIF4A2 has been implicated in translational repression and microRNA (miRNA) regulation through its interactions with the Ccr4-Not complex [51,52]. This complex is recruited to mRNAs via PABP, miRNAs, and RNA-binding proteins (RBPs), among others, when an mRNA is targeted for deadenylation and decay [53][54][55][56].…”
Section: Eif4a: a Minimal Ddx Rna Helicasementioning
confidence: 99%
See 1 more Smart Citation
“…EIF4A2 has been implicated in translational repression and microRNA (miRNA) regulation through its interactions with the Ccr4-Not complex [51,52]. This complex is recruited to mRNAs via PABP, miRNAs, and RNA-binding proteins (RBPs), among others, when an mRNA is targeted for deadenylation and decay [53][54][55][56].…”
Section: Eif4a: a Minimal Ddx Rna Helicasementioning
confidence: 99%
“…Meijer et al [57] first demonstrated that eIF4A2 activity is required for miRNA-mediated mRNA destabilization. Then, the same lab reported that eIF4A2 may exert this function by becoming incorporated into the Ccr4-Not complex and inhibiting the CNOT7 deadenylation activity or repressing translation by binding to purine-rich sequences proximal to the AUG start codon [51,52]. These experiments implicating a repressive function for eIF4A2 are at odds with eIF4A2 being able to incorporate into the eIF4F complex, which plays a stimulatory role in translation [58].…”
Section: Eif4a: a Minimal Ddx Rna Helicasementioning
confidence: 99%
“…Second, CCR4-Not promotes the degradation of inefficiently translated mRNAs by monitoring decoding rates (Webster et al, 2018;Buschauer et al, 2020). Third, together with the eIF4A2 protein, it may participate in the miRNAmediated inhibition of translation initiation of certain transcripts possessing purine-rich sequences within their 5 0 UTR (Wilczynska et al, 2019). Thus, the CCR4-Not complex is an important regulator of multiple processes, and its co-transcriptional recruitment to the nascent transcripts may profoundly impact their translation, as shown for the yeast ribosomal proteins (Gupta et al, 2016).…”
Section: Protein Factors Regulating Both Transcription and Translationmentioning
confidence: 99%
“…Initially it was shown that four yeast Not proteins were involved in the global repression of transcription initiation [11,155]. However, it now seems reasonable to suppose that the whole complex plays a role in the process [123,156]. The Ccr4-Not complex functionally and physically associates with TBP and TBP-associated components [152].…”
Section: The Ccr4-not Complex and Transcriptionmentioning
confidence: 99%